148 Buffalo city and amathole medical support initiative: quality improvement via collaborative care and education in South Africa. (16th November 2020) - Wong, Jan Man; Kumar, Arvind; Parrish, Andy
Abstract : Health inequality is an important issue in South Africa where there is a disparity between health care delivered in a rural versus urban setting. Junior doctors staff the rural clinics often with only intermittent senior support. There is no standardised support system to assist clinicians with the development of clinical skills and in one large survey only half felt they had adequate clinical supervision. Cecilia Makiwane Hospital (CMH) is a large provincial hospital situated in Mdantsane, the second largest township in South Africa. In April 2019, the Discovery Foundation provided a grant to the internal medicine team to create a systems-strengthening programme to help rural clinicians improve their clinical and non-clinical (quality improvement and teaching) skills. This became the Buffalo City and Amathole Medical Support Initiative (BAMSI), a programme with three arms: inreach, outreach and resource development. The UK Health Education England Improving Global Health (IGH) Fellowship has partnered with the hospital with successive generations of IGH fellows assisting in the creation and delivery of the programme. We describe the progress thus far of one of the arms: inreach. The development of the programme was determined by a steering committee of multi-disciplinary specialists as well as a stakeholder needs analysis. To-date, there have been fifteen doctors who have completed their inreach week. During the inreach week, participants completed a supervised audit with feedback provided by a consultant. Subsequently, a majority of participants felt an improvement in their understanding of, and ability to conduct quality improvement projects. The results thus far show that rural clinicians have a strong inclination to improve basic skills. The positivity demonstrated by doctors for quality improvement shows an opportunity to incorporate this type of training more widely in a rural setting.